Re-evaluation of lifespan in a Neotropical orchid: an eleven years survey - Rosa-Fuentes, Eddie; Tremblay, Raymond (Lankesteriana: International Journal on Orchidology, 2015)
Lifespan as a variable of the total survivorship peri- od of individuals is infrequently studied. When stud- ied it is often limited to investigation of the effect of some environmental variable on the lifespan of short lived morphological unit of the plant such as leaves or flowers.